2016
DOI: 10.2131/jts.41.207
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin induces G2/M cell cycle arrest via NAD<sup>+</sup>-dependent isocitrate dehydrogenase in human embryonic carcinoma cells

Abstract: -Organotin compounds, such as tributyltin (TBT), are well-known endocrine-disrupting chemicals (EDCs). We have recently reported that TBT induces growth arrest in the human embryonic carcinoma cell line NT2/D1 at nanomolar levels by inhibiting NAD + -dependent isocitrate dehydrogenase (NAD-IDH), which catalyzes the irreversible conversion of isocitrate to α-ketoglutarate. However, the molecular mechanisms by which NAD-IDH mediates TBT toxicity remain unclear. In the present study, we examined whether TBT at na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Thus, arresting the cell cycle is considered a very effective method for eradicating tumor cells. The G2/M phase is an important checkpoint in the cell cycle that prevents the initiation of mitosis until DNA damaged during replication is repaired (25). The majority of the cells treated with angelicin were arrested in the G2/M phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, arresting the cell cycle is considered a very effective method for eradicating tumor cells. The G2/M phase is an important checkpoint in the cell cycle that prevents the initiation of mitosis until DNA damaged during replication is repaired (25). The majority of the cells treated with angelicin were arrested in the G2/M phase.…”
Section: Discussionmentioning
confidence: 99%
“…To detect the apoptotic effects of angelicin on A549 cells, an Annexin V-FITC/propidium iodide (PI) apoptosis detection kit was used. In brief, A549 cells were seeded in a 6-well plate and incubated for 24 h; the cells were then treated with the DMSO control or angelicin (10,25 or 50 µmol) for 24 h. Next, the cells were collected, washed with PBS, and resuspended in 100 µl of 1X binding buffer. Annexin V-FITC/PI were added to each group, and the cells were incubated for 15 min at room temperature in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…TBT at 50 nM has the ability to bind to PPARγ with a higher affinity than that of the intrinsic ligands, and these genomic transcriptional activations have been reported to mediate neurodevelopmental defects 5 . To investigate the molecular mechanisms by which TBT inhibits ectodermal induction, we examined the effect of the PPARγ agonist rosiglitazone (RGZ), which had been confirmed in our previous report, as having agonistic effects on PPARγ 10 . We found that RGZ did not reduce OTX2 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the genomic effects, we previously found the non-genomic action of TBT. TBT reduced intracellular ATP levels by targeting glycolysis and mitochondrial systems, and inhibited the growth of human embryonic carcinoma NT2/D1 cells 7 10 . We also found that TBT induced the growth inhibition of human induced pluripotent stem cells (iPSCs) through mitochondrial dysfunction, such as decreased ATP levels, depolarization of mitochondrial membrane potential (MMP) and mitochondrial fragmentation, via the degradation of mitochondrial fusion factor, mitofusin1 (Mfn1) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…RT-PCR was performed as previously reported (Asanagi et al, 2016;Hirata et al, 2017). Briefly, total RNA was isolated from iPSCs using TRIzol reagent (Thermo Fisher Scientific).…”
Section: Real-time Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%